Economic Insecurity and Psychological Distress: Examining Anxiety and Depression in a Cross-Sectional Study - Muhammad Hassan Sheikh, Saira Abbas, Mian Mukhtar Ul Haq, Bilal Masood, Jay Sing, Benazir Javed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Income volatility, employment instability, and financial strain are key determinants of mental health. Using anxiety and depression, this study examines the relationship between economic insecurity and psychological distress among adults. Methodology: One-year cross-sectional study was conducted Dow University Hospital and Doctor Ruth KM Pfau Civil Hospital Karachi, from February 2022 to February 2023 and 120 adults (18–65) recruited from the community centers. For inclusion, fluency in the local language and no severe cognitive impairment were required; conditions affecting survey responses were not excluded. A composite index of income volatility, employment instability, and perceived financial strain was used to measure economic insecurity. The Generalized Anxiety Disorder 7-item (GAD-7) scale and Patient Health Questionnaire 9-item (PHQ-9) were used to assess psychological distress. The power analysis indicated that a sample size of 120 would have 80% power to detect a medium effect size (f² = 0.15) at α = 0.05. Questionnaires were collected in person and online, and the analyses were done using SPSS version 27, using Pearson correlations and regression analyses. Results: After controlling for demographics, economic insecurity predicted increased anxiety (β = 0.31, p < .001) and depression (β = 0.28, p < .001). Including it increased the variance explained by 10% for anxiety and by 8% for depression. Conclusions: The results of this study emphasize the importance of economic insecurity in mental health and call for interventions aimed to relieve both financial and psychological problems. It should be investigated in future studies in causal pathways. Overall, research is needed. Keywords: Economic Insecurity; Psychological Distress; Anxiety; Depression; Cross-Sectional Study; Income Volatility; Employment Instability; Financial Strain; Demographics; Hierarchical Regression; SPSS; Intervention; Vulnerable Populations.